A supermatrix approach provides a comprehensive genus‐level phylogeny for Gentianales. Issue 4 (23rd February 2016) - Yang, Lei‐Lei; Li, Hong‐Lei; Wei, Lei; Yang, Tuo; Kuang, Dai‐Yong; Li, Ming‐Hong; Liao, Yi‐Ying; Chen, Zhi‐Duan; Wu, Hong; Zhang, Shou‐Zhou
Abstract: Gentianales consist of Apocynaceae, Gelsemiaceae, Gentianaceae, Loganiaceae, and Rubiaceae, of which the majority are woody plants in tropical and subtropical areas. Despite extensive efforts in reconstructing the phylogeny of Gentianales based on molecular data, some interfamily and intrafamily relationships remain uncertain. We reconstructed the genus‐level phylogeny of Gentianales based on the supermatrix of eight plastid markers ( rbcL, matK, atpB, ndhF, rpl16, rps16, the trnL‐trnF region, and atpB‐rbcL spacer) and one mitochondrial gene ( matR ) using maximum likelihood. The major clades and their relationships retrieved in the present study concur with those of previous studies. All of the five families of Gentianales are monophyletic with strong support. We resolved Rubiaceae as sister to the remaining families in Gentianales and showed support for the sister relationship between Loganiaceae and Apocynaceae. Our results provide new insights into relationships among intrafamilial clades. For example, within Rubiaceae we found that Craterispermeae were sister to Morindeae + (Palicoureeae + Psychotrieae) and that Theligoneae were sister to Putorieae. Within Gentianaceae, our phylogeny revealed that Gentianeae were sister to Helieae and Potalieae, and subtribe Lisianthiinae were sister to Potaliinae and Faroinae. Within Loganiaceae, we found Neuburgia as sister to Spigelieae. Within Apocynaceae, our results supported Amsonieae as sister to Melodineae, and Hunterieae as sister to a clade comprising Plumerieae + (Carisseae + APSA). We also confirmed the monophyly of Perplocoideae and the relationships among Baisseeae + (Secamonoideae + Asclepiadoideae).